Assessment of soil dispersibility behaviour in-relation to soil internal erosion resistance / Fauzilah Ismail, Mazidah Mukri and Zainab Mohamed - Ismail, Fauzilah; Mukri, Mazidah; Mohamed, Zainab (Research Management Institute (RMI), 2008)
A study was conducted to assess soil dispersibility behaviour in-relation to soil internal erosion resistance. Dispersive soils can be a problem for many geotechnical projects and structures. Water flowing in a crack of earth dam or infiltration of rainwater through the crack of slope surface with enough erosion energy can detach the soil particles into suspension and transport it along the movement that will lead to internal erosion process. Soil samples from sloping area within UiTM Shah Alam Campus were collected and a laboratory study was carried out to assess the soil dispersibility behaviour. A laboratory pinhole test and crumb test were conducted to identify soils which are easily dispersed hence susceptible to internal erosion. Indication of the removal of soil particles during testing is a factor in assessing the possibility of internal erosion. Finegrained soils are known to have low resistance to erosion however laboratory result shows that soils fraction with high coarse-grained percentage has high dispersibility grade that lead to lower internal soil erosion resistance whereas the high moisture content percentage would enhance the dispersibility characteristic of the soils performance.